Community art festivals and sustainable rural revitalisation. Issue 11 (2nd December 2021) - Qu, Meng; Cheer, Joseph M.
Abstract: The links between art events and sustainable development in rural contexts where revitalisation is pressing is becoming increasingly obvious. The village of Mitarai is an example of a small peripheral community in Japan faced with the impacts of depopulation, ageing and socio-economic decline. The urgency to stem further regression has seen art emerge as an antidote for community strengthening. Since 2017, Shiosai, a week-long community art festival has taken place with the underlying aim to rejuvenate the area's diminishing fortunes. It exhibits artworks paying homage to local islandscapes (Cheer, Cole, Reeves & Kato, 2017 ) and employs local cultural heritage as key elements. The extent to which bottom-up art events in small rural communities can serve as a vehicle for sustainable development is examined. Findings suggest that the Shiosai drives visitation to the area and has reinvigorated latent cultural heritage. The festival stimulates inward migration and enhances community resilience and vital social capital. However, as the festival is driven from the bottom-up without external support, the extent of future local-level involvement remains a critical success factor. The implications suggest that community engagement is a vital ingredient in the mobilisation of festivals in rural contexts, as well as in ensuring that sustainable development outcomes can be optimised.